Tanggung Jawab Guru Pendidikan Agama Kristen (PAK) dalam Penanggulangan Masalah Sosial Siswa - Bangun Bangun; Bangun Munthe (Journal on Education, 2023)
The purpose of this study was to see how far the responsibility of Christian Religious Education Teachers was in overcoming social problems of students at SMP Negeri 2 Siantar. The number of samples is 54 people. This study used a descriptive method, while the data analysis carried out in the hypothesis research was Pearson's product moment correlation with the data collection tool being a questionnaire for Variable X (Teacher Responsibilities of Christian Religious Education) and Variable Y (Overcoming student social problems). To find out the extent of Christian Religious Education Teachers' Responsibilities in Overcoming students' social problems, the Pearson Product Moment Correlation Statistical Test was used. From the test results obtained a correlation test (r) 0.452 with a determination test of 20.43% and to find out whether the correlation coefficient is significant at the real level (α) = 0.05 then a "t" test is held with the test criteria if tcount obtained from the calculation greater (>) than ttable at a significant level of 1 – 0.05 with dk = n – 2 then the hypothesis is accepted and in other cases it is rejected. From the test results obtained tcount > ttable (3.6568 > 1.67), then the hypothesis is accepted. Thus it can be stated that there is a significant influence between the Responsibilities of Christian Religious Education Teachers in Overcoming students' social problems at SMP Negeri 2 Siantar.